Aspectos fenológicos, ecológicos e de produtividade da Graviola (Annona muricata L.) na região de Manaus - Falcão, Martha de Aguiar (Acta Amazonica, 2020)
Data on phenology, ecology and produtivity of the Soursop (Annona muricata L.) are here presented for the vicinity of Manaus. Flowering and fruiting are continous throughout the year with a slight flowering peak between September and January and a a slight increase in fruiting (crop) between July and September. Even though a correlation is observed between number of flowers and fruit set, the same is not true between number of flowers and mature fruit (crop) which suggests that produtivity is not limited by endogenous control. With a mean production of 16 k per tree, results are not significantly different from those observed In other regions; however, fruit size seems to be smaller than observed elsewhere. Four species of Chrysomelid beattles were found visiting the flowers.